CURRENT STATE AND DEVELOPMENT OF LAND MANAGEMENT - Taratula, Р.; Sudovyi, М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
Land management is one of the most important components of the system regulating land relations in Ukraine, because it determines formation of the structure of land use and administrative-territorial organization, preservation and protection of lands, as well as their ecosystem functions, provision of economic sectors with land resources, etc. At different times, land management pursued quite different goals and was characterized by an unequal ratio of economic, ecological and social priorities. For example, during the time of the Russian Empire, land management was mainly associated with the demarcation of land; in the Soviet period, land management had a clearly defined economic orientation with low environmental priorities; after 1990, land management began to perform a service function in relation to land reform, which was characterized by extreme socialization of land resources, reducing the economic efficiency and environmental safety of land use. By its essence, modern land management should be considered as a set of purposeful measures for placement of productive forces within the geographical environment. In modern conditions, land management has become a technical and legal basis for establishment of the rights and obligations of land owners and land users, ensuring protection of land as the main national wealth, planning development of territories, etc. At the same time, land management in recent decades has been gradually reduced to development of the most primitive types of land management documentation, which accompany the procedures for granting and seizing land plots, drawing up title documents for them. It is considered that the root cause is in the insufficient state attention to the problems of rational land use, territorial development, and limited budget funding for the effective land management. The purpose of the article is to analyze the current problems and urgent tasks of land management as a scientific basis for ecologically safe land use and state land policy in Ukraine. An important aspect is also to study the issue of increasing the efficiency of the use of production potential in agricultural production due to the rational land use and maintenance of conditions for sustainable agriculture by maximum considering the features of the natural ecological system.